ANALISA PENERAPAN POJK NOMOR 11 TAHUN 2025 DALAM PENGELOLAAN USAHA LEMBAGA PENJAMIN: An Analysis of the Implementation of POJK No. 11 of 2025 in the Management of Guarantee Institution Businesses - Abdul Hamid Arribathi; Bangkit Mulia Ramadhan (Universitas Wiralodra, 2026)
This study aims to evaluate the extent to which the guarantor institution has implemented the provisions in POJK No. 11 of 2025 concerning the Business Implementation of the Guarantor Institution and identify the challenges, adaptation strategies, and their impact on the health of the guarantor institution. This research is a qualitative-descriptive approach. The methods used are in-depth interviews (key informant interviews), observation, literature studies. The results of the study show that some guarantor institutions have taken adjustment steps in the aspects of equity requirements, risk management, claims reserves, and reporting transparency, there are major obstacles in the form of human resources, IT systems, and compliance costs. The implications of the implementation of POJK include improving the quality of governance, strengthening the credibility of the guarantor institution, but also the potential operational burden for small institutions. Research recommendations include increasing capacity building, the use of regulatory technology (regtech), as well as periodic monitoring and evaluation by the OJK.